2001
DOI: 10.1128/jb.183.8.2417-2424.2001
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment of the mecA Gene Homologue of Staphylococcus sciuri into a Resistance Determinant and Expression of the Resistant Phenotype in Staphylococcus aureus

Abstract: Strains of methicillin-resistant Staphylococcus aureus (MRSA) have become the most important causative agents of hospital-acquired diseases worldwide. The genetic determinant of resistance, mecA, is not a gene native to S. aureus but was acquired from an extraspecies source by an unknown mechanism. We recently identified a close homologue of this gene in isolates of Staphylococcus sciuri, a taxonomically primitive staphylococcal species recovered most frequently from rodents and primitive mammals. In spite of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
124
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(131 citation statements)
references
References 32 publications
4
124
0
1
Order By: Relevance
“…But S. sciuri containing mecA homolog is susceptible to methicillin. This supported that MRSA strains are descendents of ancestral strains in evolutionary process [35,36]. Staphylococcus haemolyticus (S. haemolyticus) genome carries intact IS1272 element, whereas the gene of S. aureus and S. epidermidis carries IS1272 element deleted [37].…”
mentioning
confidence: 86%
“…But S. sciuri containing mecA homolog is susceptible to methicillin. This supported that MRSA strains are descendents of ancestral strains in evolutionary process [35,36]. Staphylococcus haemolyticus (S. haemolyticus) genome carries intact IS1272 element, whereas the gene of S. aureus and S. epidermidis carries IS1272 element deleted [37].…”
mentioning
confidence: 86%
“…Polyvalent scaffolding by glycopolymers (glycolipids and glycoproteins) is a known mechanism for organizing proteins in a variety of biological processes (38,39). Whereas there are no genes of high homology to tarS in Staphylococcus sciuri, the organism from which PBP2a was speculated to derive (40,41), all deposited S. aureus strain sequences in the National Center for Biotechnology Information contain tarS. It is possible that PBP2a may exploit β-OGlcNAcylated WTAs by binding to them directly or by interacting with other cellular factors that are scaffolded by these polymers.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that many Staphylococcus epidermidis and other CoNS from human clinical isolates are resistant to methicillin [28] . An evolutionary theory proposed that S. aureus could have acquired mecA gene from S. sciuri, a species frequently isolated from animals, which harbours a close structural homologue of mecA gene [29] . These bacteria can serve as reservoirs of resistance determinants in the community, which could lead to the emergence of novel MRSA or MRS strains.…”
Section: Discussionmentioning
confidence: 99%